Trans fatty acids content of biscuits commercially available in Malaysian market and comparison with other countries - M., Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The fatty acid composition and trans fatty acid (TFA) contents of biscuits products were determined by gas chromatography, using a highly polar 100m capillary column (HP-88) and flame ionization detection. Total TFA ranged from 0.00 - 0.52 g/100 g total fatty acids and 0.12 - 0.68 g/100 g total fatty acids for local packed and unpacked biscuits, respectively. In imported biscuits, total TFA was higher ranging from 0.03 - 3.09 g/100 g of total fatty acids. Trans 16:1 was the most abundant, with values ranging from 0.01% to 38% followed by trans 18:1 Δ11 (0.01% - 13.11%), trans 18:1 Δ9 (0.01% - 4.68%), trans 18:2 (0.23% - 2.77%) and small quantities of trans 18:1 Δ6. CLA, the natural TFA constituted from 0.1% to <70% TFA. These results and comparison with published data indicate that Malaysian biscuits contained considerably low proportion of trans fatty acids following the wide use of palm fat.